2022
DOI: 10.1002/jad.12005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the severity of peer victimization and bullying perpetration among youth with interpersonal problems: A 6‐month prospective study

Abstract: IntroductionPeer victimization is prevalent and associated with adverse outcomes. In this prospective study of youth who self‐reported interpersonal problems, we examined school connectedness, school behavioral difficulties, academic difficulties, and internalizing problems (social anxiety, self‐esteem, depression) as predictors of peer victimization and bullying perpetration severity. We also examined the moderating effects of gender.MethodsParticipants were 218 youth (66.5% female), ages 12–15 years (M = 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…For instance, youth experiencing bias-based harassment based on their race, sexual orientation, gender, or religion are at greater risk for mental health challenges and increased substance use than those exposed to non-bias-based harassment (Russell et al, 2012). Further, research on bias-based harassment perpetration has found that individuals who perpetrate are also at risk of negative health functioning, including internalizing behaviors, poor mental health, and increased exposure to violence (Arango et al, 2022; Galán et al, 2021; Stuart & Jose, 2014). Some limited research has focused on youth who both are victimized and perpetrate bias-based harassment, with one study finding that this group had a particularly pronounced risk for suicidal ideation but that relative to adolescents involved as victims or perpetrators they did not report markedly more challenges in other assessed domains (including health and health care; Galán et al, 2021).…”
mentioning
confidence: 99%
“…For instance, youth experiencing bias-based harassment based on their race, sexual orientation, gender, or religion are at greater risk for mental health challenges and increased substance use than those exposed to non-bias-based harassment (Russell et al, 2012). Further, research on bias-based harassment perpetration has found that individuals who perpetrate are also at risk of negative health functioning, including internalizing behaviors, poor mental health, and increased exposure to violence (Arango et al, 2022; Galán et al, 2021; Stuart & Jose, 2014). Some limited research has focused on youth who both are victimized and perpetrate bias-based harassment, with one study finding that this group had a particularly pronounced risk for suicidal ideation but that relative to adolescents involved as victims or perpetrators they did not report markedly more challenges in other assessed domains (including health and health care; Galán et al, 2021).…”
mentioning
confidence: 99%